An examination of the International Wheelchair Rugby Federation classification system utilizing parameters of offensive game efficiency - Molik, M.; Lubelska, E.; Kosmol, A.; Bogdan, M.; Yilla, A. B.; Hyla, E. (Adapted Physical Activity Quarterly, 2008)
The purpose of the study was to examine the offensive game efficiency of elite wheelchair rugby players with regard to their International Wheelchair Rugby Federation (IWRF) classification. Male athletes (105) representing 12 European nations competing at the 2005 European Wheelchair Rugby Championships took part in this study. The primary recording instrument was the Game Efficiency Sheet (GES), an instrument designed to objectively record parameters of wheelchair rugby efficiency such as points scored, steals, turnovers, balls caught (%), and balls passed (%). Kruskal-Wallis between groups analyses identified significant differences among the lower classification groups (0.5-2.0) and between the lower and higher classification (2.5-3.5) groups. Further research is needed in identifying game efficiency differences in higher class groups.